Parliamentarism as a Legal Philosophy Subject of Analysis - Manukyan, Martin (ՀՀ ԳԱԱ)
Today, questions about what factors and conditions, legal and political institutions, and structures make this or that system democratic and the relationship between parliamentarism and the executive power continues to be the subject of heated debate. Without a truly functioning parliament and parliamentarism, it is impossible to build a democratic state governed by the rule of law, create an effective system of legislation and law, or form and develop the main elements of civil society, primarily political parties. In the article, the author puts forward the idea that understanding parliamentarism only as a form of government is insufficient. Referring to numerous definitions of parliamentarism that have existed to date and highlighting the principles of parliamentarism, the author of the article proposed his definition of parliamentarism, according to which parliamentarism is a special system of organization and functioning of state power, based on the principle of separation of powers and the rule of law, with a formally privileged position of parliament, which is elected in free elections with the participation of political parties. Այսօր էլ սուր բանավեճերի առարկա են շարունակում մնալ այն հիմնահարցերը, թե ինչպիսի գործոններ ու պայմաններ են, իրավական և քաղաքական ինստիտուտներ ու կառուցվածքներ են, որ այս կամ այն համակարգը դարձնում են ժողովրդավարական ։ Դրանցից է պառլամենտարիզմի և գործադիր իշխանության հարաբերակցությունը: Առանց իրապես գործառող պառլամենտի և պառլամենտարիզմի՝ անհնար է ժողովրդավարական իրավական պետության կառուցումը, օրենսդրության ևիրավունքի արդյունավետ համակարգի ստեղծումը, քաղաքացիական հասարակության հիմնատարրերի, հատկապես քաղաքական կուսակցությունների ձևավորումն ու զարգացումը: Հոդվածում հեղինակն առաջ է քաշում այն գաղափարը, որ պառլամենտարիզմը՝ միայն որպես կառավարման ձևի տարատեսակ հասկանալը ակնհայտորեն բավարար չԷ; Անդրադարձ կատարելով պառլամենտարիզմի վերաբերյալ մինչ այժմ եղած բազմաթիվ սահմանումն երին ևառանձնացնելով պառլամենտարիզմի սկզբունքները, հոդվածի հեղինակն առաջադրել է պառլամենտարզմի իր սահմանումը, ըստ որի՝ պառլամենտարիզմը պետական իշխանության կազմակերպման և գործառման հատուկ համակարգ է՝ հիմնված իշխանությունների տարանջատման սկզբունքի ևօրենքի գերակայության վրա, խորհրդարանի ձևական առումով արտոնյալ դիրքով, որն ընտրվում է ազատ ընտրություններով՝ քաղաքական կուսակցությունների մասնակցությամբ:
Keywords: Law